PP184 Twenty Years of Health Technology Assessments on Robotic Assisted Surgery: A Summary. (December 2021) - Forrest, Ben; Sahai, Nikhil; Song, Chao
Abstract : Introduction: Da Vinci robotic-assisted surgery (RAS) has been evaluated by health technology assessment (HTA) organizations across the world. This study aimed to analyze the existing HTA reports over years, countries, and procedures. Methods: Publicly available health technology appraisal reports on RAS published from January 2000 to November 2020 were identified via a targeted literature search. The literature search was conducted in PubMed, the Centre for Reviews and Dissemination database, the International Network of Agencies for Health Technology Assessment database, and Google scholar. Reports related to the da Vinci RAS were included. Full texts of reports were used for the analysis. For the HTAs that recommended RAS, the directional conclusion was considered as positive. For HTA reports that discouraged the use of RAS, the directional conclusion was considered as negative. The rest were considered as neutral. The reports were analyzed by year, country, and procedure. Results: We identified 65 HTA reports comprising 128 procedure-level assessments of RAS by 42 HTA organizations in 21 countries over 20 years. The annual number of assessments increased over time. The countries that completed the most assessments were Sweden (14 reports, including 15 procedure-level assessments: 13% positive and 80% neutral) and Canada (11 reports, including 20 procedure-level assessments: 65% positive). The topics of the assessments covered 27 surgical indications in urology, gynecology, thoracic, general, and ear, nose, and throat. The conclusions of the HTAs varied by surgical indication. Prostatectomy (33 reports: 85% neutral or positive) was the most widely assessed surgical indication, followed by hysterectomy (16 reports: 81% neutral or positive), nephrectomy (15 reports: 73% neutral or positive), and rectal resection (10 reports: 100% neutral or positive). Conclusions: The number and breadth of HTAs on RAS have grown at an increasing rate over the last 20 years. The directional conclusion of assessments varied by procedure and country. Further analysis is warranted to understand the factors contributing to HTA conclusions on RAS.